Taphonomy of ammonites from the Santonian-lower Campanian Santa Marta Formation, Antarctica: sedimentological controls on vertically embedded ammonites - Olivero, Eduardo Bernardo (PALAIOS)
Different morphotypes of vertically embedded ammonoid shells are abundant in the 1-km-thick deposits of the Santa Marta Formation, Antarctica, that record the evolution of a deep-water delta system. Vertical shells deposited in water depths well below the theoretical limit imposed by hydrodynamic and hydrostatic analyses are preserved as isolated specimens, dense concentrations associated with abundant wood fragments (pod preservation), or as dense concentrations inside and around large ammonites (sheltered preservation). Taphonomic analysis indicates that (1) vertical shell orientation is primary; (2) postburial reworking was minimum or absent, as indicated by consistent shell orientation parallel to regional paleocurrents and complete preservation of fragile shells with phragmocones filled with drusy calcite; and (3) vertical orientation is not biased towards a preferred morphotype. Rapid sedimentation, including deposition from high- and low-density currents, tempestites, and weak bottom currents carrying a dense suspension of ammonoid shells and wood fragments, was one of the main factors controlling the vertical preservation below the limits imposed by theoretical hydrostatic analyses. Another important factor was the plugging of the siphuncular tube with clay particles during transportation. The clay plug was stiff enough to resist the ambient hydrostatic pressure, avoiding or delaying the waterlogging of the phragmocone. Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina